Livestock production systems in the sub-humid zone of Nigeria, and ILCA's sub-humid research programme - Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1979)
Discusses the changing perceptions on the potentials of the subhumid zone of Nigeria for livestock production and includes an overview of livestock production systems in this area, with particular reference to the broad characteristic of the traditional system, constraints imposed by management, diseases & nutrition to achieve potential production capacity and constraints to development. Summarizes briefly the research proposals & work being done as part of ILCA's sub-humid research programme in this area.